Digital Dispossessions: the Importance of Regional Specificity and Sovereign Spaces to Video Game Representations of Native American Cultural Heritage - Bird, Ashlee (Studia Neophilologica, 2021)
Indigenous peoples and their cultural heritages, their ways of knowing and living, are tied to land. As Mishuana Goeman states,“Land is foundational to people’s cultural practices, and if we define culture as meaning making rather than as differentiation and isolation in a multicultural neoliberal model, thanby thinking through land as a meaning-making process rather than a claimed object, the aspiration of Native people are apparent and clear,” (Goeman, 73).Goeman asserts here that land is not limited to physical space, and that land locates a group of people physically, culturally, spiritually, intellectually,etc. and provides them with both an internal and external locus of understanding for and within broader society. When digital representations of Indigenous peoples are completely removed from any meaningful connection to their land, anerasure of culture occurs. Moreover, the physical removal of Indigenous peoples from the virtual representations of their lands is another form of dispossession and the enactment of digital Manifest Destiny. This paperutilizes a decolonial Indigenous framework to analyze the dispossessions that take place within the digital realm of the video game, why they occur so frequently, and why they are so harmful.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé